Ethical principles in practice. Evidence from participatory action research. (Kairaranga, 2008)
A significant challenge for all participants in the autism spectrum disorder participatory action research (AD PAR) project, including the Ministry of Education, the local project teams (LPT) and mentors, was the lack of availability of a single ethics approval process for the project in its entirety and, in particular, one that could accommodate the iterative, dynamic and participant-led action research process. To address this gap, participants in the AD PAR project adoptedanswer that could be routinely applied to ethical dilemmas. A guiding framework of ethical principles proved useful for participants. Central to the success of the AD PAR project was participants' ability to self-reflect, question and share resolutions. In essence, reflections on ethical dilemmas as they arose were an interwoven strand through the life cyclesof the ASD PAR project.